PRESENCE OF GLASS CEILING IN HIGHER EDUCATIONAL INSTITUTIONS: A ROADBLOCK FOR SUSTAINABLE DEVELOPMENT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The glass ceiling in higher educational  institutions is a significant roadblock to  sustainable development. Despite the  increasing number of women in faculty  positions, their career progression appears to  be slow, with many remaining concentrated  toward entry-level positions. This invisible  barrier hinders women’s advancement to top  positions, such as heads, deans, and directors. A  study of 98 faculty members working in higher  education sector in NCR region revealed that  gender and psychological constraints were the  strongest glass ceiling barriers. Other factors  like perceived discrimination and a male dominating culture significantly determine  the glass ceiling effect. The conceptual model  of the glass ceiling and career development  in the study highlights the complexities  that hinder women’s career advancement. It  offers a framework for thoroughly analyzing  and addressing these issues, considering the  interplay of societal, organizational, human,  and external factors, as well as the importance of  intersectionality and continuous adaptability.  The study points out that this vertical  segregation not only impedes individual  career development but also undermines the  broader goal of gender equality, a key aspect of  sustainable development.
Keywords: Gender inequity; Women’s leadership; Glass ceiling; Underrepresentation